Leak After Sleeve Gastrectomy: Updated Algorithm of Treatment - Manos, Thierry; Nedelcu, Marius; Nedelcu, Anamaria; Gagner, Michel; Weiss, Abdul Kader; Bastid, Christophe; Carandina, Sergio; Noel, Patrick (Obesity surgery, 2021)
Introduction Laparoscopic sleeve gastrectomy (LSG) is currently the most common procedure performed worldwide, and still the leak is considered the main limitation. After an initial enthusiasm for stents, the endoscopic treatment evolved including in the current management the septotomy with balloon dilatation and pigtails insertions. The aim of this study was to evaluate the updated algorithm of endoscopic treatment of leak following LSG including septotomy and balloon dilatation. Methods All consecutive patients treated by endoscopy between January 2018 and March 2020 for leak following LSG were included in the current study. After recording the demographic and the leak history, we have analyzed the number of endoscopic sessions, the duration of treatment, and the healing rate of endoscopic treatment for 3 groups: A, small orifice (< 10 mm); B, large orifice (> 10 mm) and acute leak; and group C with large orifice and late leak. Results A total of 53 patients received endoscopic treatment for leak following LSG. The leaks achieved complete healing after average duration of 3.2 months (range 1–7 months), 2.3 months for group A, 4.2 months for group B, and 3.7 months for group C. The average number of endoscopic procedures was 2.8 (range 2–6) and was required for general population: for group A, 2.3 sessions; in group B, 3.4 sessions; and in group C, 2.7 sessions. Two out of 53 patients (3.8%) required additional treatment outside of the current algorithm, one in group A and another in group B. One patient was transferred for pulmonary abscess, and for another patient, the leak was considered chronic after a total of 14 months, and a laparoscopic fistula-jejunostomy was performed with favorable outcomes. Conclusions Although there is still no consensus for endoscopic management of leaks after LSG, the benefits of pigtails and the septotomy are undeniable, and it should be included in the armamentarium of any bariatric endoscopic service. Graphical abstract